Understanding Attentional Modulation of Binocular Rivalry: A Framework Based on Biased Competition - Dieter, Kevin C.; Tadin, Duje (Frontiers in Human Neuroscience, 2011)
Starting from early scientific explorations of binocular rivalry, researchers have wondered about the degree to which an observer can exert voluntary attentional control over rivalry dynamics. The answer to this question would not only reveal the extent to which we may determine our own conscious visual experience, but also advance our understanding of the neural mechanisms underlying binocular rivalry. Classic studies, intriguingly, reached contradictory conclusions, ranging from an absence of attentional control, as advocated by Breese, to nearly complete control of rivalry dynamics, as reported by Helmholtz. Recent investigations have revisited this question, but the results have continued to echo the conflicting findings of earlier studies, seemingly precluding a comprehensive understanding of attentional effects on rivalry. Here, we review both classic and modern studies, and propose a unifying framework derived from the biased competition theory of attention. The key assumption of this theory is that the nature of stimulus conflict determines the limits of attentional modulation. For example, a condition in which unresolved stimulus conflict transpires through many levels of visual processing should be very susceptible to attentional control. When applied to binocular rivalry, this framework predicts strong attentional modulations under conditions of unresolved stimulus conflict (e.g., initial selection) and conditions where conflict is resolved at higher levels of visual processing (e.g., stimulus rivalry). Additionally, the efficacy of attentional control over rivalry can be increased by utilization of demanding, behaviorally relevant tasks, and likely through perceptual training paradigms. We show that this framework can help facilitate the understanding and synthesis of a diverse set of results on attentional control over rivalry, and we propose several directions for future research on this interesting topic.